Prima introduzione a Il No e il Sì di Spitz: 1970 di M.C. Aliquò e Prima introduzione a Il No e il Sì di Spitz di Massimo Fagioli - Aliquò, Maria Chiara; Fagioli, Massimo (Il sogno della farfalla, 2023)
In June 1970, the Armando publishing house printed the first Italian edition of the volume No and Yes by René A. Spitz with an introduction written by Massimo Fagioli. In these pages, the psychiatrist outlined his radical criticism towards the psychoanalytic view on child reality, affirming the profound need for a new line of research able to overcome the mere observation of overt behaviors. The text of this introduction is published for the first time in our journal, as a contribution on the author’s elaboration in the period immediately preceding the writing and publication of his masterpiece, Death instinct and knowledge.